The effects of surface compliance on greyhound galloping dynamics. (December 2019) - Hayati, Hasti; Eager, David; Walker, Paul
Greyhounds are the fastest breed of dog and can reach a speed up to 68 km/h. These racing animals sustain unique injuries seldom seen in other breeds of dog. The highest rate of life-threatening injuries in these dogs is hock fracture, mostly of the right hind-leg. One of the main injury contributing factors in this sport is the track surface. There are some studies into the ideal track surface composition for greyhound racing but almost no study has investigated the body–surface interaction. Accordingly, the purpose of this work is to study the effect of surface compliance on the galloping dynamics of greyhounds during the hind-leg single-support phase which is a critical phase in hock injuries. Thus, a three degrees-of-freedom model for the greyhound body and substrate surface is designed using spring-loaded inverted pendulum method. The results showed that forces acting on the hind-leg were substantially affected when the surface compliance altered from the relatively hard (natural grass) to a relatively soft surface (synthetic rubber). The main contribution of this work is designing a mathematical model to predict the dynamics of the hock and the hind-leg as the most vulnerable body parts in greyhounds. Furthermore, this model can be used to optimise the greyhound track surface composition and therefore improve the safety and welfare within the greyhound racing industry.